Nanotechnology for brain tumor imaging and therapy based on π-conjugated materials: state-of-the-art advances and prospects - Sun, Wenshe; Wang, Congxiao; Tian, Chuan; Li, Xueda; Hu, Xiaokun; Liu, Shifeng (Frontiers in Chemistry, 2023)
In contemporary biomedical research, the development of nanotechnology has brought forth numerous possibilities for brain tumor imaging and therapy. Among these, π-conjugated materials have garnered significant attention as a special class of nanomaterials in brain tumor-related studies. With their excellent optical and electronic properties, π-conjugated materials can be tailored in structure and nature to facilitate applications in multimodal imaging, nano-drug delivery, photothermal therapy, and other related fields. This review focuses on presenting the cutting-edge advances and application prospects of π-conjugated materials in brain tumor imaging and therapeutic nanotechnology.